The Use of Natural Lighting in Students’ Hostels: A Case Study of Ayeduase, a Suburb of Kumasi, Ghana (Journal of Science and Technology, 2016)
The role that natural lighting plays in buildings cannot be underestimated. Natural light is integrated into buildings because of its potential economic benefit and the effect on the occupants’ psychological and physiological well-being. This study concentrates on Ayeduase, a suburb of Kumasi, Ghana, where students live in hostels with poor architectural design. Therefore, the primary aim of this study is to investigate the health and visual comfort of students living in Ayeduase, by creating awareness of the positive effects of natural light on humans. Questionnaires and interviews, as well as empirical measuring of daylight levels in the spaces of selected hostels were used. Analysed data revealed that the level of illuminance in the hostels is considerably poor and this resulted in students using artificial lighting throughout the day. Nevertheless, the negative effect of this situation can be prevented from occurring in further developments in Ayeduase (and Ghana as a whole), by educating designers on the benefits of using natural lighting in buildings and by enforcing laws that will ensure that buildings have maximum openings that allow enough daylight into the interior spaces. These measures will help reduce utility costs, improve the well-being of building occupants and increase the performance of students.